Clinical assessments in psychiatry : mastering skills and passing exams - Tampi, Rajesh R.; Muralee, Sunanda; Weder, Natalie D.; Wilkins, Kirsten M. (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins, 2010)
"This book contains case vignettes and discussions to help residents, fellows, and practitioners maximize their competency in performing clinical assessments in psychiatry. Derived from a highly successful course at Yale University, the book focuses on the key clinical skills emphasized by the American Board of Psychiatry and Neurology in residency training and on the oral board examination. These skills include physician-patient relationship; psychiatric interview, including mental-status exam; case presentations; live patient; case formulation; differential diagnosis; and treatment interventions. Dr. Tampi's training in the U.S., U.K., and India enables him to cross cultures around the globe. A companion website will contain videos demonstrating interview skills and patient assessments."--BOOK JACKET.
Preparing for clinical examinations in psychiatry -- Conducting the psychiatric interview -- Case vignettes and discussions.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Psychiatry -- Examinations -- Study guides; Electronic books